Międzynarodowe normy płynności jako uzupełniające miary bezpieczeństwa banku oraz sektora bankowego - Ivanna Chaikovska (Finanse i Prawo Finansowe, 2022)
The purpose of the article is to assess the security of Polish listed banks and the entire banking sector in terms of their liquidity. This article characterizes the liquidity of the Polish banking sector and Polish listed banks in the years 2009–2019.